Effect of pruning and plant density on melon grown in greenhouse conditions - Díaz Alvarado, Jorge Manuel (2017)
The effect of three planting densities (1,9, 3,2 and 3,9 plants/m2) and three pruning methods (one secondary shoot; two secondary shoots; and no pruning) on the yield and quality of Honey Dew cantaloupe JMX-701 F-1 (Cucumis melo L. var. inodorus), there were evaluated. The harvest started late with a highest planting density, compared with otherdensities. There were not significant differences statistically among treatments for yield (total and marketable). There were significant differences statistically among treatments for the number of fruit per plant (total and marketable): 0,66 and 0,64 fruit/plant (respectively) were harvested the highest planting density (3,9 plants/m2), whereas 1,17 and 1,08 fruit/plant (respectively) were gathered with 1,9 plants/m2. The best treatment was no pruning at 1,9 plants/m2, as it entails low production cost.